Implementasi Low Power pada Sensor Node dengan Protokol Komunikasi Zigbee - Frans Herbert Nainggolan; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Changing times are increasingly rapid due to the development of information technology. It is estimated, the development of the use of market places from the Internet of Things will be more widespread. For this reason, the government itself has launched the Making Indonesia 4.0 program, where the component is the Internet of Things. The application of the Internet of Things in Indonesia can be done in aspects of transportation, health, the environment, and others. Not without negative impacts, the development of the Internet of Things (IoT) also brings negative impacts, one of which is huge energy consumption. Xbee is a module that is used as a radio communication media with the zigbee 802.15.4 protocol. Xbee can also be configured with several types of features, one of which is the active period where the device is transmitting and in the active period where all devices and microcontrollers can be turned off. From this problem, the implementation of low power sensor nodes in the zigbee communication protocol is designed.The system design with the xbee-s1 communication module is designed in 1 coordinator node, and 3 end nodes that are connected to the arduino uno microcontroller, the DHT-11 sensor, and the LDR sensor in charge of taking sensor data values ​​both temperature, humidity and light resistance value. After being tested to get the results the system can run as expected, with the result of a decrease in the value of the current of 0.031 A or 11.23%.